1995
DOI: 10.1159/000188756
|View full text |Cite
|
Sign up to set email alerts
|

Nephrosis in Childhood

Abstract: Succinct aspects of clinical features, pathophysiology and prognosis of nephrotic syndrome in childhood, and indications for performing renal biopsy are enumerated in this review. Orthodox treatment of the nephrotic syndrome with more recent therapeutic approaches, and the role of diuretics, albumin infusions and immunizations in patients with the nephrotic syndrome are reviewed. The etiology of peritonitis, acute renal failure, and renal transplantation are re-examined to update nephrologists on the associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 45 publications
0
17
0
2
Order By: Relevance
“…every other day for 6 months, has been advocated by Mendoza et al [168]who had shown good responses. Others [169]have advocated the additional use of cyclosporin A at 5–7 mg/kg/day for 8 weeks. This treatment regimen has been successful in some patients with nephrotic syndrome from focal glomerulosclerosis, especially during the earlier stages of focal glomerulosclerosis.…”
Section: Treatmentmentioning
confidence: 99%
“…every other day for 6 months, has been advocated by Mendoza et al [168]who had shown good responses. Others [169]have advocated the additional use of cyclosporin A at 5–7 mg/kg/day for 8 weeks. This treatment regimen has been successful in some patients with nephrotic syndrome from focal glomerulosclerosis, especially during the earlier stages of focal glomerulosclerosis.…”
Section: Treatmentmentioning
confidence: 99%
“…However truly acute "intrinsic" renal failure is an uncommon complication of this disease, especially in children [1,2,3,4]. A clear explanation for the development of severe renal failure in these patients is rarely found, but in most cases clinical improvement with supportive therapy suggests unknown and transient deleterious phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…anemia, persistent hypocomplementimia with persistent raised serum creatinine and high cholesterol, unfavorable age (<2 years and >8 years) are regarded as bad prognostic features 1,2,7,10 . So, it is importancte to correlate the biochemical and hematological parameters with the prognosis of the disease.…”
Section: Resultsmentioning
confidence: 99%
“…Primary or idiopathic nephrotic syndrome is commonly seen in 95% of patients 6 , 80% of whom show histological features of minimal change nephrotic syndrome (MCNS) and have good prognosis [7][8] . Although recurrence is common in nephrotic syndrome, 90-95% of children with MCNS are responsive to steroid therapy with complete clinical and biochemical remission and have excellent long term prognosis 2,6,7,9 . Steroid sensitive nephrotic syndrome (SSNS) comprises 80-90% of nephrotic syndrome and rest 10-20% nephrotic syndrome is steroid resistant (SRNS) 10 .…”
mentioning
confidence: 99%